Patterns and gaps in guideline-directed statin use for atherosclerotic cardiovascular disease by race and ethnicity - Ashish Sarraju; Xiaowei Yan; Qiwen Huang; Ramzi Dudum; Latha Palaniappan; Fatima Rodriguez (Elsevier, 2024)
Objective: There remain disparities by race and ethnicity in atherosclerotic cardiovascular disease (ASCVD). Statins reduce low-density lipoprotein cholesterol (LDL-c) and improve ASCVD outcomes. ASCVD treatment patterns across disaggregated race and ethnicity groups are incompletely understood. We aimed to evaluate statin use and LDL-c control for ASCVD by race and ethnicity. Methods: From an electronic health record (EHR)-based cohort from a multisite Northern California health system, we included adults with an ASCVD diagnosis from 2010 to 2021 and at least 2 primary care visits, stratified by race and ethnicity (Non-Hispanic White [NHW], Non-Hispanic Black [Black], Hispanic, and Asian). Hispanic (Mexican, Puerto Rican, Other) and Asian (Asian Indian, Chinese, Filipino, Japanese, Korean, Vietnamese, Other) groups were disaggregated. Primary outcomes were 1-year post-ASCVD statin use (prescription) and LDL-c control (at least one value <70 mg/dL). Adjusted odds ratios (ORs) were estimated using logistic regression. Results: Of 133,158 patients, there were 89,944 NHW, 6,294 Black, 12,478 (9.4 %) Hispanic and 13,179 (9.9 %) Asian patients. At 1 year after incident ASCVD, there was suboptimal statin use (any statins <60 %, high-intensity <25 %) and LDL-c control (<30 %) across groups, with lowest proportions in Black patients for statin use (46.7 %, any statin) and LDL-c control (10.7 %, OR 0.89 (0.81-0.97), referent NHW). Disaggregation of Asian and Hispanic groups unmasked within-group heterogeneity. Conclusions: In patients with incident ASCVD, we describe suboptimal and heterogenous 1-year post-ASCVD guideline-directed statin use and 1-year post-ASCVD LDL-c control across disaggregated race and ethnicity groups. Findings may improve understanding of ASCVD treatment disparities and guide implementation.